Effects of polymerization medium on electrical conductivity and optical properties of organic semiconductor-based polypyrrole - Yakuphanoğlu, Fahrettin; Aydin, Mehmet Enver (Wiley, 2007)
The effects of tetrabutylammonium tetrafluoroborate (TBAFB), tetrabutylammonium hexafluorophosphate (TBAPF(6)), and paratoluene sulfonoicacid (PTSA) polymerization mediums on the electrical conductivity and optical properties of the polypyrrole (PPy) have been investigated. The electrical conductivity and optical properties of the samples polymerized in presence of TBAFB, TBAPF6, and PTSA organic salts change with medium of prepared polymer. The electrical conductivity of the TBAFB, PTSA, and TBAPF6 samples at 27 degrees C were found to be 3.43 x 10(-1), 4.48 x 10(-2), and 1.60 x 10(-4) (S/cm), respectively. The lowest optical band gap of the polymer was found to be 2.23 eV. The refractive index dispersion of the samples obeys single oscillator model. The obtained results suggest that polymerization medium changes electrical conductivity and optical properties of the PPy.
Keywords: Electrode Materials; Transition